2014
DOI: 10.19026/ajas.6.4851
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Improved Maize Seed Varieties in Southern Zambia

Abstract: Maize is the principal agricultural crop produced by Zambian smallholder farmers for household consumption and sale. Their production strategy is therefore important in meeting food security and income needs. This study uses data collected from a survey of a random sample of farm households in southern Zambia to develop a Tobit regression model. The model identifies farm and farmer characteristics important for adoption of improved maize seed varieties as well as to determine the role of farmer perceptions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 9 publications
3
22
0
2
Order By: Relevance
“…These farmers mainly cultivated improved seeds with a higher yield per hectare and achieved higher sales. These farmers own more land, consistent with Kalinda et al (2014) finding that improved corn seed use is directly related to the size of land owned. However, these farmers are risk acceptors, as they had more resources to mitigate the effects of risks when adopting new technologies.…”
Section: Profile Of Corn Farmer Segmentssupporting
confidence: 81%
“…These farmers mainly cultivated improved seeds with a higher yield per hectare and achieved higher sales. These farmers own more land, consistent with Kalinda et al (2014) finding that improved corn seed use is directly related to the size of land owned. However, these farmers are risk acceptors, as they had more resources to mitigate the effects of risks when adopting new technologies.…”
Section: Profile Of Corn Farmer Segmentssupporting
confidence: 81%
“…For example, Salifu, Alhassan, and Salifu (2015) used a logit model to analyze the determinants of adoption of improved maize varieties in the Wa municipality in Ghana and found that marital status, characteristics of improved seeds, age, education level, and experience in cultivating maize by the household head had a significant effect on the adoption of improved maize varieties. Additionally, Kalinda, Tembo, and Kuntashula (2014) using a Tobit model found that sex, membership in a peasant organization, farm size, and favorable perceptions towards the potential yields of improved maize varieties and the price of their output positively and significantly affected the adoption of improved maize varieties. In Cameroon, past studies have identified education level, marketing orientation, membership in farmer organizations, farm size and contact with extension agents as factors of adoption of improved maize varieties (MabahTene, Havard, & Temple, 2013;Ntsama Etoundi & Kamgnia Dia, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These results are reinforced by various authors in different conditions such as the case of Zambia presented by Kalinda et al (2014) where they conclude that the adoption of improved seeds showed a positive relation with the size of the farm or that for estates rented or greater than one hectare, farmers prefer to invest in improved seed with the whole technological package to ensure the yields (Sserunkuuma, 2005).…”
Section: Typification Of Farmers By Categorymentioning
confidence: 87%
“…Estos resultados son reforzados por diversos autores en diferentes condiciones como por ejemplo el caso de Zambia presentado por Kalinda et al (2014) donde concluyen que la adopción de semillas mejoradas mostró una relación positiva con el…”
Section: Typification Of Farmers By Categoryunclassified